Effect of 32-Weeks High-Intensity Interval Training and Resistance Training on Delaying Sarcopenia: Focus on Endogenous Apoptosis - Su, Hao; Wen, Tianhao; Liu, Dongsen; Shao, Jia; Zhao, Lei; Gao, Qi (Frontiers in Physiology, 2022)
The present study aimed to investigate the effects of 32 weeks of high-intensity interval training (HIIT) and resistance training (RT) on the skeletal muscle-related indices and provide a theoretical basis for regulating the mitochondrial-mediated pathway to delay sarcopenia. We randomly selected 10 from eight-month-old male SD rats (N=130) as the baseline group; the rats were sacrificed. The remaining rats were randomly assigned to one of three groups: control group (C, n = 40, natural aging for 32 weeks), HIIT group (H, n = 40, performed 6 loops of 3 min at 90% and 3 min at 50% VO2max speed treadmill running, with 5 min at 70% VO2max speed at the beginning and the end of the training, 3 times a week for 32 weeks), and resistance group (R, n = 40, 46 min per day, three days per week, with a 30% maximum load on a treadmill with a slope of 35°, 15 m/min). The soleus muscles were collected for analysis at baseline and every 8 weeks. Aging resulted in decreased soleus muscle mass and Bcl-2 levels in the mitochondria, while the levels of reactive oxygen species (ROS) and Bax did not change. HIIT reversed the age-associated activation of pro-apoptotic processes, but RT did not. In addition, when rats were aged from 8 to 16 months, the level of Cyt-C did not change, the Caspase-9 levels and Caspase-3 levels decreased gradually in the soleus muscles, the rats of both the HIIT and RT groups had these indices decreased at 32 weeks. The results suggest that the age-associated loss of muscle mass was reversed by training, and the effect of RT was better than that of HIIT. An age-associated increase in apoptotic processes may occur in rats over 16 months of age. However, both the HIIT and RT rats showed a decrease in the apoptosis of skeletal muscle cells after 32 weeks of intervention. Although HIIT performed better for long-term intervention regarding the pro-apoptotic factors, there was no difference in the effect of HIIT and RT on apoptosis at 32 weeks.